Leituras que se entrelaçam: um estudo sobre as relações entre o leitor ficcional, o leitor real e o letramento literário no ensino médio - Lima, Bonfim Queiroz (2020)
The present work seeks to understand what relationships can be established between the real reader and the fictional reader in literary reading, verifying whether these relationships interfere in the literary literacy process. In this sense, it was sought to carry out a critical description of academic texts that deal with the reader in literature and of literature; to ascertain how contemporary literary works construct, by means of characters that represent the alterity of the reader, an image of literary reading; to identify what relationships are established between the real reader and the fictional reader in literary reading and to investigate whether these relationships interfere in the literary literacy process. The research developed was of a qualitative nature, with a methodological focus on phenomenology. It was opted to conduct a case study involving bibliographic and documentary research. The methodological instruments used cover a variety of techniques and procedures, typical of qualitative studies, they were used during the research: questionnaires and open structured interviews; diary production and field notes on reading workshops and informal conversations with the subjects surveyed; documental and bibliographic analysis (theoretical texts, literary works, official documents, activities and texts produced by the students). The study was conducted in two different moments: firstly it was sought to raise how the literary reader was fictionalized in two contemporary narratives: As pedras não morrem (The Stones Do Not Die) (2004), by Miriam Mambrini and O leitor do trem das 6h27 (The reader of the train of the 6h27) (2015), by Jean-Paul Didierlaurent. Afterwards, a case study was carried out with 42 students from a first grade class of high school in a state school in the town of Xinguara, state of Pará. During the case study, literary literacy workshops were developed based on the proposals of Professor Rildo Cosson (2012), in which the students read the examined works. From the analysis of the data generated in this research, it was found the determinant role of subjectivity in the establishment of relations in the act of reading. It was possible to ascertain that there was the identification of the real reader with the character reader and the importance of the affectivity in this process. It was also observed the realization of two types of readings triggered from the works read: the mimetic readings and the informative readings; in addition to a large number of indications of possible readings. It was also found that the fact that the students already have the habit of performing literary readings allowed a greater constancy in the establishment of these relationships, that is, all those who had declared a higher amount of readings performed in the period Investigated were able to establish and demonstrate a large number of analyzed relationships. However, the fact that they do not have this habit is not determinant, since some students who declare themselves not readers have also shown high scores. It is heightened, therefore, that the establishment of these relationships, as well as the formation of the community of readers, contribute to the process of literary literacy of the students.